(untitled) (Revista Contexto & Educação, 2023)
This study aims to present the scenarios of public higher education financing policies in the years 2010 and 2020 and establish a comparative relationship with the investments of the public power in the Federal University of Pelotas (UFPEL) in the years 2010 and 2020. Analyzes scientific articles produced by researchers in the field on this period and compares them with the Management Reports of UFPEL. It starts from the concept of structural crisis to understand the way out of the crisis through neoliberalism, which also affects educational institutions, especially public ones, which have their resources sequestered due to the financial reorganization that governments practice to contain spending on public services. In the end, the article concludes that there is a gap in financial resources for public universities, at the same time that there is promotion of the private network of higher education, which grows more in relation to IFES. It also concludes that despite the growth in the number of IFES in 10 years, it is not linear, as the student, faculty and technical-administrative body has decreased at UFPEL.